Close Cassini flybys of Saturn’s ring moons Pan, Daphnis, Atlas, Pandora, and Epimetheus - Buratti, Bonnie Jean; Thomas, P. C.; Roussos, E.; Howett, C.; Seiß, M.; Hendrix, A. R.; Helfenstein, P.; Brown, R. H.; Clark, R. N.; Denk, T.; Filacchione, G.; Hoffmann, H.; et al. (Science, 2019)
Cassini's last look at Saturn's rings - During the final stages of the Cassini mission, the spacecraft flew between the planet and its rings, providing a new view on this spectacular system (see the Perspective by Ida). Setting the scene, Spilker reviews the numerous discoveries made using Cassini during the 13 years it spent orbiting Saturn. Iess et al. measured the gravitational pull on Cassini, separating the contributions from the planet and the rings. This allowed them to determine the interior structure of Saturn and the mass of its rings. Buratti et al. present observations of five small moons located in and around the rings. The moons each have distinctive shapes and compositions, owing to accretion of ring material. Tiscareno et al. observed the rings directly at close range, finding complex features sculpted by the gravitational interactions between moons and ring particles. Together, these results show that Saturn's rings are substantially younger than the planet itself and constrain models of their origin. - Science, this issue p. 1046, p. eaat2965, p. eaat2349, p. eaau1017; see also p. 1028 - Structured Abstract - INTRODUCTIONSaturn’s main ring system is associated with a family of small moons. Pan and Daphnis orbit within the A-ring’s Encke Gap and Keeler Gap, respectively, whereas Pandora and Prometheus orbit just outside the F-ring and Atlas just outside the A-ring. The latter three moons help to confine ring particles.The moons Janus and Epimetheus are in closely spaced orbits that they exchange approximately every 4 years; these two objects may be collisional fragments of a larger body. All these moons have densities much less than 1000 kg/m3, indicating that they formed from ring debris that accumulated around a preexisting core. - RATIONALEDuring the final stages of the Cassini mission, the spacecraft made a series of close observations of Saturn’s rings. Flybys of Pan, Daphnis, Pandora, Atlas, and Epimetheus were performed to investigate the geologic processes shaping their surfaces, their composition, their thermal and ultraviolet properties, their relationship to Saturn’s ring system, and their interactions with particles in Saturn’s magnetosphere. - RESULTSThe moons that orbit in ring gaps or are adjacent to the main rings have equatorial ridges of material consisting of accreted particles that are distinct from their rounded central cores. The cores are more structurally sound than ridges, with rougher surfaces and more impact craters. Complex patterns of grooves formed by tidal stresses crisscross the moons.A visible-infrared reflectance spectrum of Pan, which is embedded in the rings, shows that it is redder than any of the other ring moons. The color of the moons becomes more red as the distance to Enceladus increases. This suggests that the optical properties of the moons are determined by the balance of two external effects: addition of a red coloring agent from the main rings, and accretion of neutral-colored icy particles or water vapor possibly from the E-ring, which is formed by Enceladus’s plume. The exact composition of the red material from the main ring system is unknown, although a mixture containing organic silicates and iron is likely. Differences in particle size also affect the moons’ spectra.Measurements of the spectral slope of Epimetheus in the ultraviolet suggest that it is less affected by particles from the E-ring than are the mid-sized main moons farther from Saturn. Temperature maps were derived for both Atlas and Epimetheus, whose blackbody temperatures were 82 ± 5 K and 90 ± 3 K, respectively.Carbon dioxide, which is present on the eight mid-sized saturnian moons, was not detected on the ring moons, nor were any volatiles other than water ice. Measurements showed a scarcity of high-energy ions in the vicinity of the ring moons and only transient energetic electron populations; in the ring gaps, no trapped electron or proton radiation was detected. Although particle bombardment alters both the albedo and color of the main moons’ surfaces, for the ring moons it appears to be unimportant. - CONCLUSIONSaturn’s ring moons record a complex geologic history with groove formation caused by tidal stresses and accretion of ring particles. The moons embedded within the rings or near their edges have solid cores with equatorial ridges of more weakly consolidated material. The finding of a porous surface further supports substantial accretion. High-resolution images strongly suggest exposures of a solid substrate distinct from the mobile regolith that frequently covers essentially all small Solar System objects. These exposures may eventually help to reveal systematic trends of the evolution of moons and their geologic structures for the whole of Saturn’s satellite system. Download high-res image Open in new tab Download Powerpoint The A-ring “shepherd” moon Atlas showing ridges of accumulated ring particles.(A) Visible-light image of Atlas showing the core and equatorial ridge. (B) Infrared image of the moon at 2.0 μm. (C) Thermal infrared scan of Atlas consistent with a mean temperature of 82 ± 5 K. - Saturn’s main ring system is associated with a set of small moons that either are embedded within it or interact with the rings to alter their shape and composition. Five close flybys of the moons Pan, Daphnis, Atlas, Pandora, and Epimetheus were performed between December 2016 and April 2017 during the ring-grazing orbits of the Cassini mission. Data on the moons’ morphology, structure, particle environment, and composition were returned, along with images in the ultraviolet and thermal infrared. We find that the optical properties of the moons’ surfaces are determined by two competing processes: contamination by a red material formed in Saturn’s main ring system and accretion of bright icy particles or water vapor from volcanic plumes originating on the moon Enceladus. - Five small moons located close to Saturn’s rings have unusual morphologies, contain water ice, and have accreted ring material. - Five small moons located close to Saturn’s rings have unusual morphologies, contain water ice, and have accreted ring material.
Gesehen am 13.12.2019